Practices of Compassion : An Exploration and Experience - Bryant, M. Darrol,; Maniates, Yanni,; Tulku, Lama Doboom, (Brill | Manohar Publishers & Distributors, 2018)
This volume grew out of a remarkable Contemplative Seminar on Practices of Compassion held in Hyderabad at the end of January 2016. The event was initiated by Lama Doboom Tulku, organized by World Buddhist Culture Trust and conducted by Professor M. Darrol Bryant. Unlike typical conferences, this event incorporated practices of compassion led by participants from their own spiritual practices. Each day began and ended in silence, the participants sat in silence, danced together, shared spiritual practices and learned from one another. Papers were written and circulated in advance. There was no reading of papers, but only discussion. It proved to be a deeply moving experience of practices of compassion for all the participants. At the end of the seminar, there was a spontaneous conviction that this experience and exploration of compassion should be shared with a wider audience. There were contributions from Buddhist, Christian, Hindu, Muslim, Jain, Sikh, Jewish, and other spiritual streams. Later some additional contributions were invited as well. The volume is a many-leafed flower exhibiting the rich diversity of practices of compassion found in the human family. It is also a testimony to the centrality of silence as the way to compassion. It is the journey within that manifests in actions without. It is not a conceptual journey but a journey of the heart.